IMPLEMENTASI GERAKAN SAYANG IBU (GSI) DI DESA TASIK SEMINAI KECAMATAN KOTO GASIB TAHUN 2015 - Asrida, Wan; Mi’raj, Mhd. Wahyudin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The purpose of this study was to determine and analyze the implementation of maternal affection movement in Tasik Seminai Village Koto Gasib subdistrict year 2015. To improve the quality of women and reduce the number of maternal and infant mortality then under the Act the Minister of Women's Empowerment Child Protection of the Republic of Indonesia Number 2 Year 2007 on the revitalization of the Movement dear mother, then Siak based Siak Regency Decree No. 146 / HK / KPTS / 2015 on the Establishment of the steering committee secretariat and Improvement Mothers movement. In this case the relevant agencies in the implementation of Mothers movement is the Child Protection Agency for Women's Empowerment and Family Planning Siak, which in the implementation of interrelated between district, sub-district to the village as a target implementation. The phenomenon shows still not optimal implementation of Mothers movement activities in every village it can be seen from the activities carried on. The place where you are investigating is the Office of Child Protection of Women Empowerment and Siak Family Planning, Koto Gasib sub-district office, health center of Koto Gasib and Tasik Seminai Village. Who became informants in this study are those directly involved in the implementation of policies, namely Head of Women Empowerment Child Protection and Family Planning, chief of BP3AKB part Improved quality of life of women, the Head of the Koto Gasib Sub-district and Secretary of Koto Gasib, Head of Health Center of Koto Gasib, Head of Tasik Seminai Village.From the research that author did then obtained some conclusions that the implementation of government policies in the implementation of Mothers movement in Siak not optimum. It can be seen from Tasik Seminai Village of Koto Gasib sub-district in its implementation is still not understand the people on Mothers movement that is still low public support and also not optimal activities Mothers movement that are conducted in Tasik Seminai Village.Keywords: Implementation, Mothers movement.